PENGARUH KEPEMILIKAN MANAJERIAL, PROFITABILITAS DAN UKURAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN - Dewi, Sukmawati; Syahzuni, Barlia Annis (Jurnal Riset Akuntansi Politala, 2024)
The aim of the research is to examine the relationship between managerial ownership, profitability and company size and company value in the non-cyclical consumer sector which is listed and active on the Indonesia Stock Exchange (IDX). The use of causality research design in this research is to look for cause and effect relationships. The panel data regression method obtained a sample of 69 observation data which combined cross-section data from 23 companies with time-series data for three years from 2020 to 2022. The data in the research was processed using statistical analysis tools. The best random effect model was selected from the results of the Chow test, Hausman test and Lagrange multiplier test and has passed the classical assumption test. Data processing shows that partially managerial ownership and company size are proven to be unable to have a significant influence on company value. Meanwhile, the profitability variable is able to influence company value in a positive direction. It is hoped that the research results can help companies maintain factors that can optimize company value and help investors consider relevant factors in investment decisions.